Klasifikasi Tingkat Kepuasan Masyarakat terhadap Pelayanan Pembuatan KTP Elektronik di Dinas Dukcapil Semper Barat Menggunakan Metode Naïve Bayes - Lestari, Dinny Amalia; Sugiyono, Sugiyono; Akbar, Yuma; Hidayat, Aditya Zakaria (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
Population administration plays an important role in Indonesia as it is involved in various activities at the government agency level. Based on data from 2020, the population in Jakarta reached 2,343,511 people. This indicates that the government in every region must provide the best service in managing population administration, especially in the issuance of electronic ID cards (e-KTP). However, various issues have been found that lead to public dissatisfaction, such as the lengthy service process, lack of information, and limited number of service personnel. Therefore, it is necessary to conduct an analysis of the level of public satisfaction to evaluate and improve service quality. This research aims to classify the level of satisfaction of the community regarding the service of e-KTP issuance. The object of this study is the community members who are applying for electronic ID cards at the Dukcapil Semper Barat. The method used in this research is a quantitative approach, with data collection through questionnaires distributed to 100 respondents. Data is obtained using questionnaires distributed to the public, and subsequently analyzed through classification performance evaluation processes. The results of this study indicate that the Naïve Bayes method is capable of classifying the level of public satisfaction with a fairly good accuracy rate. These findings are expected to serve as a reference for the Dukcapil in improving the quality of public services sustainably.